The Dhaka water services turnaround. - Sharma,Manoj (Asian Development Bank, 2017)
ADB investment program in the Dhaka Water Supply and Sewerage Authority (DWASA) provided a breakthrough in approaching urban development, particularly the delivery of clean, reliable, affordable water and to the poor, no less. And not just a breakthrough for Dhaka or the rest of Bangladesh, but for the region of South Asia. This publication looks at the key success factors that other utilities are taking note of: The zonal approach to rehabilitating and managing urban water services, trenchless technology for expeditiously laying pipes, and how to connect the urban poor and keeping them connected through community managed approaches.